A Novel Paradigm for Sex Chromosome Turnover: Y and W Changes, X and Z Remain. (27th July 2020) - Ezaz, Tariq
Abstract : On the Black Swans of conventional sex determination theory: There aren't many, but when an exception to the standard model of sex determination (evolutionary turnover of genes playing the role of "master sex determiner") arises, it certainly screams out for an explanation. In this issue, a novel one is put forward. It now awaits testing, particularly at the population level.